Reflective writing in counselling and psychotherapy - Wright, Jeannie; Bolton, Gillie (SAGE, 2012)
This book provides a straightforward route into the essentials of keeping a personal development portfolio or reflective journal for all counselling and psychotherapy trainees, whether they are approaching the topic from a psychodynamic, person-centred or CBT perspective